(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This symposium will present evidence, expertise, and experiences from different European countries on the implementation and effectiveness of Physical Activity Referral Schemes (PARS) and the development of relevant guidelines and implementation standards for physical activity promotion. Description: Promoting physical activity through healthcare professionals is a key strategy for improving population activity levels, as highlighted in the WHO’s Global Action Plan on Physical Activity (GAPPA) and the Physical Activity Strategy for the WHO European Region 2016–2025. PARS are considered a promising approach to integrating physical activity promotion into routine clinical practice. However, although PARS aim to support sustained behaviour change, evidence of their effectiveness remains mixed, probably due to differences in programme content and delivery, as well as the lack of standardised guidelines. This symposium examines five initiatives that address these challenges. Evidence from Belgium and Germany highlights the potential of PARS to promote long-term physical activity improvements, with additional gains in psychosocial determinants such as motivation, self-efficacy, and health competences. In the Netherlands, the launch of an online consultation guideline (“Bewust Bewegen”) enables healthcare professionals to integrate brief, evidence-based physical activity advice into daily practice. Another German initiative focuses on developing practical, interdisciplinary guidelines for the promotion of physical activity in rehabilitation settings, ensuring alignment with real-world clinical needs. Finally, Scotland’s national evaluation of its PARS standards shows high adoption of behaviour change principles, but also identifies barriers to routine data collection that limit robust outcome evaluation. Conclusion: These contributions demonstrate that PARS and related guidelines can effectively support the promotion of physical activity within healthcare systems. However, their long-term success depends on sustained implementation efforts, professional support, and standardised approaches to monitoring and evaluation. By sharing lessons learned across countries, this symposium offers valuable insights into how healthcare systems can better embed physical activity promotion into practice to improve patient outcomes and public health.